2019
DOI: 10.1038/s41387-019-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visceral fat measurement by dual-energy X-ray absorptiometry to computed tomography in HIV and non-HIV

Abstract: Background/Objectives Individuals with HIV are susceptible to visceral fat accumulation, which confers an increased risk of cardiometabolic disease. Advanced software to ascertain visceral fat content from dual-energy X-ray absorptiometry (DXA) has not been validated among this population. We sought to compare DXA with computed tomography (CT) in the measurement of visceral fat cross-sectional area (VAT) in HIV and non-HIV using Bland–Altman analyses. Subjects/Methods D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…However, the agreement between methods varied considerably, with DXA estimating lower or higher VAT values than MRI or CT without a clear pattern, possibly because GE systems estimate total VAT, whereas Hologic assesses the area in the L4/L5 intervertebral space. Although four reports showed overestimation by DXA (8,(33)(34)(35), in four studies, DXA underestimated CT/MRI values (6,9,24,36), as in the current investigation. A report in which DXA underestimated MRI by 30% (6) agrees with lower DXA VAT than MRI VAT values in APS (141 vs. 167 cm 2 ).…”
Section: Re Sultssupporting
confidence: 56%
See 1 more Smart Citation
“…However, the agreement between methods varied considerably, with DXA estimating lower or higher VAT values than MRI or CT without a clear pattern, possibly because GE systems estimate total VAT, whereas Hologic assesses the area in the L4/L5 intervertebral space. Although four reports showed overestimation by DXA (8,(33)(34)(35), in four studies, DXA underestimated CT/MRI values (6,9,24,36), as in the current investigation. A report in which DXA underestimated MRI by 30% (6) agrees with lower DXA VAT than MRI VAT values in APS (141 vs. 167 cm 2 ).…”
Section: Re Sultssupporting
confidence: 56%
“…Among nine previous reports in adults, five studies compared VAT by DXA with CT measures (24,(33)(34)(35)(36) and four with MRI measures (6)(7)(8)(9). Of these, four used Hologic (7,24,34,36) and five GE (6,8,9,33,35) systems for DXA assessment. All correlations were strong and highly significant (r > 0.90).…”
Section: Re Sultsmentioning
confidence: 99%
“…Further studies of quantifying the SAT in the android region may help to confirm or exclude this source of error. Fourman et al found an overestimation of SAT combined with an underestimation of VAT compared to a single image CT in humans by using a Hologic Horizon A DXA scanner [29].…”
Section: Discussionmentioning
confidence: 99%
“…InnerCore also has overestimated VAT cross sectionally in children (13). In longitudinal studies, InnerCore has underestimated changes in VAT compared with CT (11) and lacked validity for estimating changes in VAT in children (13).…”
Section: Introductionmentioning
confidence: 99%